Use of Triamcinolone in keloid - B., Shwetha; D. C., Sathyaki (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Keloids are well known for recurrence. There is no standardized regimen for the treatment of keloids. Many different treatment modalities such as surgical excision, intralesional corticosteroids, radiotherapy, and pressure earrings have been used for keloids. Surgical excision alone may result in recurrence rate of 40-100%. Many different modalities of treatment have been tried to prevent recurrence. Aims and objectives of the study was to evaluate the efficacy of Triamcinolone in preventing recurrence of Keloid. Methods: 40 patients who underwent excision of keloid at a tertiary care centre. Surgery alone was performed in 20 patients and surgery with post operative intra lesional Triamcinolone injection was given weekly interval for 6 weeks in another 20 patients. Patients were followed up for the period of 2 years Results: Recurrence was found in 5 patients who underwent excision alone and there was no recurrence among patients who received post operative intra lesional triamcinolone. Conclusions: Multi modality treatment is better to prevent recurrence of Keloid.